Description of Family Welfare Counseling through Bina Keluarga Balita (BKB) Services - Putri Julita Mina Harafah; Irmawita Irmawita (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2019)
This research is motivated by the success of the Bina Keluarga Balita (BKB) Taruko I Korong Gadang Village, Kuranji Sub-District, Padang City, as seen from the high percentage of the presence of mothers or families participating in these activities and achievements achieved by BKB. Researchers suspect that the cause of the BKB's success was due to the guidance of family welfare carried out. The purpose of this study was to describe the material, media/APE, and attitudes of workers/cadres and participants in the guidance of family welfare. This type of research is quantitative descriptive research. The population in this study were 49 families of BKB. The sampling technique is clusster random sampling of 30 people. Questionnaire technique in collecting data with a tool list of statements. Techniques for analyzing data with percentages. The results showed that family welfare guidance through BKB services, namely: (1) material in BKB family welfare guidance was good, (2) educational media/games were categorized very well, and (3) attitudes of educators/cadres and participants were classified as very good.Keywords: Guidance, Family Welfare, BKB